ErbB4 affects Th1/Th17 cell differentiation and promotes psoriasis progression: ErbB4 promotes psoriasis progression - Tang, Rongrong; Cui , Haiyan; Dou, Rongrong; Tao, Lin; Tan, Linlin; Guo, Ting; Luo, Dan (Cellular and Molecular Biology, 2023)
Psoriasis seriously harms people’s physical and mental health. More and more people pay attention to improving the psoriasis process by immune cells. Our study alters the course of psoriasis by discovering the effect of ErbB4 on the ratio of Th1/Th17 cells. We detected the expression of ErbB4 in CD4-positive T cells in peripheral blood of clinical patients and clinical samples by qPCR and detected the expression of ErbB4 in mouse samples of the model group. ErbB4 siRNA was designed and transfected into cells. The effect of ErbB4 siRNA on Th1/Th17 cell ratio was observed by flow cytometry. ErbB4 siRNA was transfected into mice by lentivirus infection to observe its effect on psoriasis. Finally, the mechanism of ErbB4 affecting psoriasis was observed by Western Blot. According to the results, ErbB4 is highly expressed in clinical samples of psoriasis and CD4-positive T cells of patients with psoriasis. Inhibition of ErbB4 expression can reduce the proportion of Th1/Th17 cells, improve the pathogenesis of psoriasis and have therapeutic effect on psoriasis. Western Blot results showed that ErbB4 affected psoriasis through the IL23/IL17A signal axis. Our study demonstrates that ErbB4 could be a potential immune target for the treatment of psoriasis.